Topography of as built surfaces generated in metal additive manufacturing: A multi scale analysis from form to roughness - Cabanettes, F.; Joubert, A.; Chardon, G.; Dumas, V.; Rech, J.; Grosjean, C.; Dimkovski, Z. (Precision engineering, 2018)
•Multi scale topography measurements are performed on as-built SLM surfaces.•Different building inclinations are observed.•Different surface generation phenomena are emphasized at different scales.•Some parameters are found to be good indicators of typical signatures of AM surfaces.•Correlations between the building inclination and the topography skewness or Rsm are found. Topographies are one of the challenges for the development of the metal additive manufacturing promising technique. The article investigates multi scale topographies (from form to roughness) of as built surfaces generated by selective laser melting (SLM). Different building inclinations of samples were observed both for upskin and downskin surfaces with a wide range of measuring techniques. The two main aims are: (i) to make a critical review of measuring techniques at different scales, (ii) to enlighten the different surface generation phenomena (and the corresponding scale) occurring during additive manufacturing. The effect of heat treatment on each scale of the topography is also discussed. It is found that the focus variation technique is well suited for AM surfaces. Concerning the observation of the inclined surfaces, some parameters are emphasized as good indicators of typical signatures of AM surfaces: isotropy for the weld track component, the skewness and Rsm for the staircase effect, fractal dimension for the presence of partly melted particles. The different parameters studied helps to model and understand the different surface generation phenomena aforementioned.